THE INFLUENCE OF ART MOTIF BATIK MEGA MENDUNG CIREBON TO FESYEN IN JAKARTA - Riyanti, Menul Teguh; Rouselyn, Melisha (International Journal of Research -GRANTHAALAYAH, 2018)
Development of fashion and fashion is growing very rapidly. Indonesia’s population of 242 million is a very large business opportunities in the field of fashion. This market share not only contested by foreign businessmen, as designers from France, Japan, Korea and even China. With increasing competition in the domestic fashion, then the local designers have to work hard to improve the competitiveness of both the face of the market share within and outside the country. Diverse effort is made to provide a reliable characteristic as an attraction by fashion designers in the country such as administering local elements in works such as weaving, batik, traditional motifs and others. One effort to give a traditional touch in the design of clothing as well as promoting one motif mega cloudy to improve the competitiveness of fashion in Indonesia as well as abroad, Melisha Rousellyn along with Menul Teguh Riyanti tried to apply the art of batik mega cloudy in the work of fashion. One effort to give a traditional touch in the design of clothing as well as promoting one motif mega cloudy cirebon in order to improve the competitiveness of fashion in Indonesia as well as abroad. Changes batik originally sacred to the development of contemporary batik into fashion. Batik is one of Indonesia’s cultural products.